COMMUNICATION CONTEXTUALITY IN THE NETWORK - Іщук, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article summarizes the features of the Network interpretation processes in order to identify patterns of formation of its semantic field. Interpretation in the Network takes place on a polycontextual basis, through the association of transpersonal and personal contexts. Transpersonal contexts increase individual features of interpretation and are connected with specificity of virtual, interactive, multimedia communication. Personal contexts, on which ways of interpretation of the text significantly depend, contain implicit (mental), explicit (external) contexts of the addressee and the circumstances of their interpretation. It is substantiated that the Internet communication is carried out on a plural basis that promotes spiritual development and at the same time can generate a hermeneutical dissonance.